Recycling of yeast multifunctional autolysates and extracts in the food industry - Kuntsova Mariia; Meledina Tatiana; Davydenko Svetlana (E3S Web of Conferences, 2024)
Recycling of industrial waste is one of the most crucial problems for the food industry. The forces of modern researchers are focused on solving this problem and using the biopotential of spent resources. Residual yeast from fermentation industries, in particular brewing, is of particular interest among the variety of food production waste. This is due to the extremely rich chemical composition of the yeast cell, and the possibility of obtaining a wide range of ingredients that exhibit both biological activity and technologically significant properties. Spent brewer's yeast is rich in proteins and carbohydrates, as well as vitamins B and minerals. The protein fraction, which accounts for 45–60% by dry weight (dw), contains all essential amino acids in sufficient quantities, which allows considering this secondary material resource an excellent source of protein with high biological value and a well-balanced AA profile. The carbohydrate fraction, comprising approximately 40% by dw, consists of intracellular carbohydrates (such as simple sugars and glycogen) as well as cell wall polysaccharides (such as β-glucan and α-mannan). Special emphasis is placed on the cell wall components due to their significant multidirectional biological activity and technologically important properties. Thus, β-glucan and α-mannan, along with emulsifying, sorbing and stabilizing properties, exhibit antioxidant and antimicrobial activity, immunomodulatory and prebiotic properties. This review presents an analysis of yeast autolysates and extracts sources as well as the influence of cultivation conditions and production methods on their chemical composition.